Possible Protective Anticancer effect of Ethanol Fraction of Iraqi Hibiscus Tiliaceus L. Leaves Extract on Diethylnitrosamine-induced Hepatocarcinogenesis in Male Rats - Maan Abdul-Azeez, Zahraa; Hattab Mutlag, Shihab (Iraqi Journal of Pharmaceutical Sciences, 2023)
Abstract Liver cancer with hepatocellular carcinoma a serious clinical illness that progresses quickly and has a bad prognosis because to increased malignancy. Fibrosis is the precursor of liver cancer, which progresses to cirrhosis and carcinoma Diethylnitrosamine (DEN) is a chemical molecule that has been used as a carcinogenic agent to promote cancer in test animals because of its strong carcinogenic potential. Herbal plants have long been used as inexpensive, effective alternatives to pharmaceuticals in various liver-associated complications, since they contain many bioactive compounds useful in liver disorders. Hibiscus tiliaceus L. (Malvaceae) contain various phytochemicals in the plant extracts such as Flavonoids, phenols, alkaloids, Tannins, Saponins, Quinones, Coumarine, Triterpenoids, glycosides and Steroids. Thus, has various health benefits, and have medicinal and therapeutic values, It could be a source of natural antioxidants, antimicrobials, hepatoprotective compounds, and antimutagenic effects.The study was designed To study the possible protective role of Iraqi Hibiscus tiliaceus L. ethanol leaves extract administered in two different doses on diethylnitrosamine induced liver carcinoma in male Wistar Albino rats. Rats utilized in this study were randomized into 4 groups (six rats per each group); Group I: (Control) Rats were administered oral daily dose of 1ml /kg/day of distilled water for 20 weeks; Group II: rats intraperitoneally injected with 70 mg/kg diethyl nitrosamine once per week for 10 continuous weeks; Group III: Rats were administered 250mg/kg of Iraqi Hibiscus tiliaceus L. ethanol leaves extract as chronic oral administration with food for 5 days per week for 20 weeks and subsequently intraperitoneal dose of diethylnitrosamine (70 mg/kg) once per week for 10 continuous weeks; Groups IV: Rats were administered 500mg/kg of Hibiscus tiliaceus L. ethanol leaves extract as chronic oral administration with food for 5 days per week for 20 weeks with subsequently intraperitoneal dose of diethylnitrosamine (70 mg/kg) once per week for 10 continuous weeks. The finding revealed that Iraqi Hibiscus tiliaceus L. ethanol leaves extract showed significant reduction (P<0.05) in malondialdehyde, alpha fetoprotein (AFP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), total bilirubin (TSB), pro-inflammatory cytokines include transforming growth factor beta (TGFβ), tumor necrosis factor alpha (TNFα) and significant elevation (P<0.05) of anti-oxidant enzyme superoxide dismutase (SOD) in dose dependent manner. In conclusion this study demonstrated that the chemoprotective role of Hibiscus tiliaceus L. ethanol leaves extract might be explained by; lowered levels of hepatic enzymes, pro-inflammatory cytokines, and antioxidant levels, as well as decreased levels of alpha fetoprotein (AFP), the gold standard for detecting hepatocellular carcinoma.